2021
DOI: 10.1097/sla.0000000000004902
|View full text |Cite
|
Sign up to set email alerts
|

Sutured Versus Mesh-augmented Hiatus Hernia Repair

Abstract: Objective: This meta-analysis systematically reviewed published randomized control trials comparing sutured versus mesh-augmented hiatus hernia (HH) repair. Our primary endpoint was HH recurrence at short- and long-term follow-up. Secondary endpoints were: surgical complications, operative times, dysphagia and quality of life. Summary Background Data: Repair of large HHs is increasingly being performed. However, there is no consensus for the optimal tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The overall rate of 34% of hiatal hernia recurrence for both groups at 13 years after the operation might be considered high, but other randomized trials with long-term follow-up have shown similar or even higher rates . Likewise, in a recent meta-analysis of randomized clinical trials with long-term follow-up, 30.7% and 31.3% recurrence rates were reported after mesh augmentation and after suture repair only, respectively . Most information regarding durability of hiatal hernia repair emanates from studies of patients with large paraesophageal hiatal hernias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of 34% of hiatal hernia recurrence for both groups at 13 years after the operation might be considered high, but other randomized trials with long-term follow-up have shown similar or even higher rates . Likewise, in a recent meta-analysis of randomized clinical trials with long-term follow-up, 30.7% and 31.3% recurrence rates were reported after mesh augmentation and after suture repair only, respectively . Most information regarding durability of hiatal hernia repair emanates from studies of patients with large paraesophageal hiatal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…Early randomized trials with short-term outcomes reported lower rates of hiatal hernia recurrence in patients with mesh reinforcement compared with crural closure using sutures only . However, more recent studies with longer follow-up did not show significant differences . Moreover, the use of mesh in the hiatal orifice carries the risk of serious complications, such as esophageal stenosis, mesh erosion, or fibrosis, leading to persistent dysphagia or pain …”
Section: Introductionmentioning
confidence: 99%
“…8 Finally, some surgeons routinely use mesh to buttress the crural closure as mesh may decrease the incidence of early recurrence at cost of increased rates of early dysphagia and no decrease in the incidence of long-term recurrence. [9][10][11][12][13] Approaches toward postoperative care including discharge also vary. Same day discharge has been found to be both feasible and safe with an associated decrease in hospital costs.…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects of this article deserve comments. Most of the studies mentioned in the discussion evaluated the use of mesh for the repair of large paraesophageal hernias, a different disease and a more complex operation, whereas in this study, only patients mostly with small sliding hernias were included . In addition, only 40% of the original patients were assessed for hiatal hernia recurrence at the long-term follow-up.…”
mentioning
confidence: 99%
“…Analatos and colleagues must be congratulated for this long-term follow-up study that shows that mesh repair did not reduce hernia recurrence when compared with suture repair of hiatal hernias. This study confirms the results of many other studies that have shown that a cruroplasty with sutures is as effective as a cruroplasty reinforced by either absorbable or nonabsorbable mesh …”
mentioning
confidence: 99%